PENGARUH RASIO KEUANGAN DAN EPS TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR - Mochammad Zainil Achyar, 08.05.51.0076 (Students Journal of Economic and Management, 2013)
This study aimed to examine the effect of financial ratio and earning per share (EPS) on stocj return in the Indonesia Stock Exchange (IDX) registered betwen 2009-2011 on the stock exchange. The number of samples obtained under these categoriesÂ amounted to 125 sharesof the company. The data is sampled using purposive sample jugement method. The re4sult of this study using multiple regression find that only two variables (leverage and EPS) that signidficantly affect the following year stock return with level of significance 5 percent.Keywords: return stock, leverage, likuidity, profitability and EPS.